Ambulatory treatment in the management of pneumothorax: A systematic review of the literature - Brims, Fraser; Maskell, N. (BMJ Group, 2013)
Introduction: Spontaneous pneumothorax (SP) is broken down into primary (PSP: no known underlying lung disease), secondary (SSP: known lung disease) and from trauma or iatrogenic pneumothorax (IP). Current treatments include a conservative approach, needle aspiration, chest drain, suction and surgery. A Heimlich valve (HV) is a lightweight one-way valve designed for the ambulatory treatment of pneumothorax (with an intercostal catheter). Methods: We performed a systematic review across nine electronic databases for studies reporting the use of HV for adults with pneumothorax. Randomised controlled trials (RCT), case control studies and case series were included, unrestricted by year of publication. Measures of interest included the use only of a HV to manage SP or IP, (ie, avoidance of further procedures), successful treatment as outpatient (OP) and complications. Results: Eighteen studies were included reporting on the use of HV in 1235 patients, 992 cases of SP (of which 413 were reported as PSP) and 243 IP. The overall quality of the reports was moderate to poor with high risk of bias. Success with HV alone was 1060/1235 (85.8%) and treatment as OP successful in 761/977 (77.9%). Serious complications are rare. Long-term outcomes are comparable with current treatments. Conclusions: High-quality data to support the use of HV for ambulatory treatment of pneumothorax is sparse. The use of HV in such circumstances may have benefits for patient comfort, mobility and avoidance of hospital admission, with comparable outcomes to current practice. There is urgent need for a carefully designed RCT to answer his question.